Analisis Kerusakan Struktur Bangunan dan Manajemen Bencana Akibat Gempa Bumi, Tsunami, dan Likuifaksi di Palu - Sudarno P Tampubolon; I Putu Ellsa Sarassantika; I Wayan Gede Suarjana (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
The strong column-weak beam is a design concept that needs to be implemented and considered in the planning of building structures (high-rise and low-rise buildings). Generally, structural failure occurs at beam-column joints. Such failure occurred due to the lack of attention to good and correct design concepts. The detailing of reinforcement for columns, beams, and beam-column connections has not yet fully implemented the SNI-2847-2019 standard which results in the reinforcement cannot withstand the combination of tensile, compressive, and shear forces that occur during an earthquake. In addition, the incomplete design of strong column-weak beam in building planning causes the building to fail in the column structure when receiving axial forces. The purpose of this study was to analyze the structural damage and the disaster management system applied during the earthquake in Palu. The research is carried out by investigation/survey methods on the study area as well as checking and recording the data about damage condition of buildings and conducting a hammer test (non-destructive test) to get the strength value of the concrete. Testing result showed the compressive strength value of the f’c concrete used is 20 to 48 MPa. In addition, the details of stirrups reinforcement are also not fully understood about their function on beams and columns, which results in the installation of stirrup reinforcement does not meet the criteria for bending angles of 90˚, 135˚, 180˚ and the addition of tensile and compressive reinforcement lengths. The high potential for earthquake hazard causes Palu and its surroundings tend to have an earthquake risk. For this reason, it is necessary to implement disaster mitigation for Palu region, which aims to reduce the number of casualties when natural disasters occur, both human and property loses.